2020
DOI: 10.3390/cryst10070628
|View full text |Cite
|
Sign up to set email alerts
|

Pump-Probe Time-Resolved Serial Femtosecond Crystallography at X-Ray Free Electron Lasers

Abstract: With time-resolved crystallography (TRX), it is possible to follow the reaction dynamics in biological macromolecules by investigating the structure of transient states along the reaction coordinate. X-ray free electron lasers (XFELs) have enabled TRX experiments on previously uncharted femtosecond timescales. Here, we review the recent developments, opportunities, and challenges of pump-probe TRX at XFELs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 114 publications
0
16
0
Order By: Relevance
“…There are several parameters that need to be considered and carefully tuned for a successful pump-probe TR-SFX experiment. The most obvious are the timing synchronization between the optical laser "pump" and the FEL "probe", the optical laser power, the materials used for the fabrication of the injection device and the optical density or the thickness and size of the microcrystals [18,23,54,[59][60][61][62]. The synchronization of the X-ray FEL and optical laser pulses is critical for the accurate measurement of delay time points for experiments targeting the dynamics of timescales from fs to a few ps and hence, the data interpretation of the pump-probe SFX experiments, particularly for the instruments that run at a megahertz repetition rate [11,54,60].…”
Section: Tr-sfx With Light-responsive Biomacromoleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several parameters that need to be considered and carefully tuned for a successful pump-probe TR-SFX experiment. The most obvious are the timing synchronization between the optical laser "pump" and the FEL "probe", the optical laser power, the materials used for the fabrication of the injection device and the optical density or the thickness and size of the microcrystals [18,23,54,[59][60][61][62]. The synchronization of the X-ray FEL and optical laser pulses is critical for the accurate measurement of delay time points for experiments targeting the dynamics of timescales from fs to a few ps and hence, the data interpretation of the pump-probe SFX experiments, particularly for the instruments that run at a megahertz repetition rate [11,54,60].…”
Section: Tr-sfx With Light-responsive Biomacromoleculesmentioning
confidence: 99%
“…As a result, the optimal photoexcitation wavelength and the duration of the photo-intermediates can be determined prior to the pump-probe TR-SFX experiment, thereby assisting in the experimental design [61,64,66,67]. Grünbein et al reported comprehensive details of the guidelines and parameters that need to be considered for the photo-excitation setup during pump-probe TR-SFX experiments [62]. As an example, to study the light-induced structural changes of photosystem (PSII) upon two flash (2F) excitation, Shen and co-workers used an ATR-FTIR difference spectroscopy with similar pump laser setup to study the system both in solution and crystalline forms.…”
Section: Tr-sfx With Light-responsive Biomacromoleculesmentioning
confidence: 99%
“…By now, numerous biomolecular structures have been studied, elucidated, and updated with TR-SFX using the six currently operational hard X-ray XFEL facilities worldwide ( 29 ). Some reports included light-induced excitation of photoactive proteins such as photosystems I and II ( 30 , 31 , 32 , 33 ), the photoactive yellow protein ( 34 , 35 , 36 ), bacteriorhodopsin ( 37 , 38 ), and, more recently, phytochrome proteins ( 39 ). Another widely used method for TR-SFX is known as mix and inject serial crystallography (MISC) whereby a substrate is mixed with protein crystals directly before interacting with the XFEL beam, allowing structural changes to be studied in minutes to sub-millisecond timescales ( 40 , 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pump-probe measurements have been used to explore the dynamic properties of the interaction of materials, such as interfaces, defects, and surfaces on material properties [4]. This technique has been used extensively for data collection in both solid-state materials [4] and biological materials [5,6]. A pump pulse (laser pulse) initiates dynamics and after a controllable time delay, a probe pulse (X-rays) is used to characterize the resultant change.…”
Section: Introductionmentioning
confidence: 99%